PERAN LEMBAGA OMBUDSMAN DAERAH ISTIMEWA YOGYAKARTA DALAM MENDORONG TERWUJUDNYA ETIKA USAHA YANG BAIK - Laurentius Banyu Biru (Penerbit Universitas Atma Jaya Yogyakarta, 2022)
This research was inspired by the existence of the DIY Ombudsman Institute which has one of the goals of encouraging the realization of business ethics. There are 2 (two) issues raised in this study, namely: What is the role of the DIY Ombudsman Institute in encouraging the realization of business ethics and what are the criteria for the DIY Ombudsman Institute in identifying a case as a violation of business ethics in terms of Utilitarianism and Deontology ethical theory? This research is a normative research with a statutory approach and a philosophical approach. The results showed that the DIY Ombudsman Institute carried out its role by socializing and facilitating the resolution of business ethics violations. The results of the study also show that the Yogyakarta Ombudsman Institute uses the criteria of violating obligations in determining a case to constitute a violation of good business ethics.